2007
DOI: 10.1111/j.1440-1754.2007.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental metabolic alkalosis

Abstract: We present a newborn with hypochloraemic metabolic alkalosis due to severe metabolic alkalosis of his mother. Hypoventilation as a leading symptom resolved quickly with treatment but may be life-threatening if not detected. In this case, the mother had a probable eating disorder. Little is known about transplacentally acquired electrolyte disorders in this setting. In the absence of symptoms, most of the cases might be undetected. The usual neonatal outcome of anorexia and/or bulimia nervosa in pregnancy is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…65,67 Although large studies have not shown an overall micronutrient deficiency in patients with eating disorders in pregnancy, there have been reports of an increase in the risk of neural tube defects in offspring of women with self-reported dieting behaviors in the first trimester and of hypochloremic metabolic acidosis in a newborn due to severe eating disorder-related maternal metabolic alkalosis. 68,69 Offspring of women with active or remitted eating disorders are more likely to be small for gestational age and have a lower birth weight than population norms. 63,65,70,71 One case series of infertile women exemplified these risks, with 12 births from 14 women with eating or exercise disorders resulting in four newborns less than 2,500 g. 48 Offspring also tend to have smaller head circumferences, a higher risk of microcephaly, and a higher risk of birth defects, especially those born to women with anorexia nervosa diagnoses and low pregnancy weight gain.…”
Section: Risks In Pregnancymentioning
confidence: 99%
“…65,67 Although large studies have not shown an overall micronutrient deficiency in patients with eating disorders in pregnancy, there have been reports of an increase in the risk of neural tube defects in offspring of women with self-reported dieting behaviors in the first trimester and of hypochloremic metabolic acidosis in a newborn due to severe eating disorder-related maternal metabolic alkalosis. 68,69 Offspring of women with active or remitted eating disorders are more likely to be small for gestational age and have a lower birth weight than population norms. 63,65,70,71 One case series of infertile women exemplified these risks, with 12 births from 14 women with eating or exercise disorders resulting in four newborns less than 2,500 g. 48 Offspring also tend to have smaller head circumferences, a higher risk of microcephaly, and a higher risk of birth defects, especially those born to women with anorexia nervosa diagnoses and low pregnancy weight gain.…”
Section: Risks In Pregnancymentioning
confidence: 99%
“…Vomiting is common in pregnancy but significant vomiting with a marked alkalosis is very uncommon and only three cases have been described previously. [2][3][4] One further case of metabolic alkalosis was associated with pica and oral bicarbonate ingestion. 5 Consideration of the cause of vomiting was also required, and the worsening of her symptoms, in combination with right upper quadrant pain, leucocytosis, deranged renal and liver function, prompted the clinical team to consider a diagnosis of acute fatty liver of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The three previous published cases were all identified because of neonatal illness, including a neonate with hypoventilation and episodic cyanosis and a significant alkalosis at birth, associated with maternal hypochloraemic alkalosis (pH 7.63, PaCO 2 7.0 kPa, HCO 3 – 34.6 mmol/L, base excess 10.5 mmol/L, Cl – 84 mmol/L, K + 1.5 mmol/L), thought to have resulted from an eating disorder. 2 The second describes a neonate with respiratory distress, possible sepsis and significant alkalosis immediately following birth. The mother had a hypochloraemic alkalosis (pH 7.57, PaCO 2 7.0 kPa, HCO 3 – 48 mmol/L, Cl – 78 mmol/L, K + 1.7 mmol/L), thought to be the result of reduced oral intake and vomiting as an attempt to conceal her pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe hyperemesis during pregnancy or alcoholism can also develop in the adult with PBS (1). In the pediatric field, neonatal-onset PBS has been anecdotally reported who were born to mothers with eating disorders and resultant malnutrition (6,7).…”
Section: Introductionmentioning
confidence: 99%